Ternary precursor material, ternary positive electrode material and preparation method and application of ternary precursor material and ternary positive electrode material
By using ternary precursor materials of active metal hydroxide and oxalate coating in single crystal ternary positive electrode materials, combining acid-base neutralization reaction and two-stage sintering process, the problem of poor material dispersion is solved and improved The electrochemical performance and stability of lithium-ion batteries.
Patent Information
- Application Number
- CN202411317927.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-20
AI Technical Summary
The existing single-crystal ternary cathode materials have poor agglomeration and dispersion during the preparation process, which affects the electrochemical performance of lithium-ion batteries.
Using active metal hydroxide as the matrix and active metal oxalate as the ternary precursor material for the coating layer, the clad oxalate is deposited in situ through acid-base neutralization reaction, and combined with the two-stage sintering process, the single crystal three is improved. Dispersion and compaction density of the element cathode material.
It significantly improves the dispersion and compaction density of single-crystal ternary cathode materials, improves the electrochemical performance and cycle stability of lithium-ion batteries, and reduces production costs.
Smart Images

Figure CN119306261A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion battery materials, and specifically relates to a ternary precursor material, a ternary positive electrode material, and a preparation method and application thereof. Background Art
[0002] In recent years, lithium-ion batteries have become the most promising energy devices in the world's science and industry due to their high energy density, long cycle life and good safety performance. Among the many cathode materials for preparing lithium-ion batteries, ternary cathode materials have received widespread attention due to their high reversible capacity, good safety and relatively low cost.
[0003] Generally, single crystal ternary cathode materials are primary particles without grain boundaries, which have high crystallinity and strong mechanical strength. Compared with traditional polycrystalline ternary cathode materials, single crystal ternary cathode materials have better surface chemical stability and high-temperature storage performance, which is conducive to improving the mechanical stability of cathode materials during charge and discharge cycles, and effectively inhibiting the capacity decay of lithium-ion batteries. Dispersibility is one of the important technical indicators of single crystal ternary cathode materials. Highly dispersed single crystal particles can significantly improve the tap density and compaction density of ternary cathode materials, and reduce microcracks caused by anisotropy during the cycle.
[0004] The precursors required for preparing single-crystal ternary materials are usually small-diameter spherical particles, and the dispersibility of the precursor particles has a direct impact on the dispersibility of the single-crystal ternary materials. At the same time, the excellent dispersibility of the single-crystal ternary materials will have an important impact on the electrochemical performance of the lithium-ion batteries prepared from them. Most of the single-crystal ternary precursor particles prepared by the commonly used coprecipitation reaction have the problems of small particle size, large specific surface area, easy agglomeration and difficulty in rapid dispersion, which further affects the dispersibility of the positive electrode material, making the electrochemical performance of the lithium-ion batteries prepared from them worse.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] In view of the problems of easy agglomeration and poor dispersibility of single-crystal ternary positive electrode materials prepared by the prior art, the purpose of the present invention is to provide a ternary precursor material, a ternary positive electrode material and a preparation method and application thereof, aiming to improve the dispersibility and compaction density of the ternary positive electrode material and further improve the electrochemical performance of lithium-ion batteries.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a ternary precursor material, comprising a substrate and a coating layer on the surface of the substrate, wherein the substrate is an active metal hydroxide, and the coating layer is an active metal oxalate; the active metal comprises nickel, cobalt, manganese and N; and the N is selected from one or more doping elements selected from magnesium, copper, aluminum, titanium, tantalum or niobium.
[0008] In an optional embodiment, the median particle size of the ternary precursor material particles is 5 μm to 7 μm.
[0009] In an optional embodiment, the carbon content of the ternary precursor material particles is 0.2% to 0.5%.
[0010] In a second aspect, the present invention provides a method for preparing a ternary precursor material, the preparation method comprising the following steps: The oxalic acid solution is added into the dispersion of the active metal hydroxide, and the mixture is stirred for reaction to obtain a ternary precursor material.
[0011] In an optional embodiment, the preparation method of the active metal hydroxide includes: dissolving nickel salt, cobalt salt, manganese salt, and N salt in water to obtain a metal salt solution, and then adding the metal salt solution, complexing agent and precipitant to a reactor with pure water as the base liquid to carry out a co-precipitation reaction.
[0012] In an optional embodiment, the nickel salt, the cobalt salt, and the manganese salt include at least one of a sulfate, a chloride, and a nitrate.
[0013] In an alternative embodiment, the N salt comprises at least one of soluble salts of magnesium, copper, aluminum, titanium, tantalum and niobium.
[0014] In an optional embodiment, the sum of the molar concentrations of nickel ions, cobalt ions, manganese ions and N ions in the metal salt solution is 1.5-2.5 mol / L.
[0015] In an optional embodiment, in the metal salt solution, based on the total molar number of metal salts being 100 mol, the molar ratio of the nickel salt, the cobalt salt, the manganese salt and the N salt is (35-90): (6-35): (3-35): (1-5).
[0016] In an optional embodiment, the complexing agent is aqueous ammonia with a molar concentration of 4 to 6 mol / L.
[0017] In an optional embodiment, the precipitant is a sodium hydroxide solution or a potassium hydroxide solution with a molar concentration of 9 to 11 mol / L.
[0018] In an optional embodiment, the pH value of the coprecipitation reaction is 9-12, the reaction temperature is 40-70° C., the reaction time is 48-72 h, and the reaction stirring rate is 300-600 r / min.
[0019] In an optional embodiment, the mass concentration of the oxalic acid solution is 100-500 g / L, and the mass of oxalic acid in the oxalic acid solution is 10%-80% of the mass of the active metal hydroxide.
[0020] In an optional embodiment, the stirring reaction temperature is room temperature and the reaction time is 4 to 8 hours.
[0021] In a third aspect, the present invention provides a ternary positive electrode material, which is obtained by mixing the ternary precursor material described in the first aspect with a lithium source and sintering the mixture.
[0022] In an optional embodiment, the lithium source includes at least one of lithium hydroxide, lithium acetate and lithium oxalate.
[0023] In an optional embodiment, the ratio of the total molar number of the active metal elements to the molar number of the lithium element is 1:(1-1.05).
[0024] In an optional embodiment, the sintering includes two stages of sintering. The first stage is to heat the temperature to 650°C~750°C at a heating rate of 3~5°C / min, and keep it warm for 3~5 hours in an oxygen atmosphere. The second stage is to heat the temperature to 900°C~1000°C at a heating rate of 7~9°C / min, and keep it warm for 9~11 hours in an oxygen atmosphere. After cooling to room temperature, the sintered product is crushed, ground and sieved through a 400-mesh sieve.
[0025] In a fourth aspect, the present invention also provides an application of a ternary positive electrode material in a prepared lithium-ion battery.
[0026] Compared with the prior art, the present invention has the following beneficial effects: (1) The ternary precursor material prepared by the present invention has a matrix and a coating layer, wherein the matrix is an active metal hydroxide and the coating layer is an active metal oxalate. When subsequently sintered with a lithium source, the active metal oxalate can decompose and produce gas to form a pore structure during the sintering process. The pore structure can increase the pores between the primary particles, thereby improving the dispersibility of the single crystal ternary positive electrode material. In addition, the coating matrix uses active metal hydroxides to ensure a high tap density and compaction density of the single crystal ternary positive electrode material. In summary, the present invention combines the respective advantages of active metal oxalates and active metal hydroxides to obtain a single crystal ternary positive electrode material that is highly dispersed and has a high compaction density.
[0027] (2) The present invention adds oxalic acid solution to the dispersion of active metal hydroxide, utilizes the acid-base neutralization reaction between oxalic acid and active metal hydroxide, and in situ deposits and coats a layer of active metal oxalate on the surface of the active metal hydroxide. The preparation method has simple process, mild reaction conditions, low production cost, and is easy for industrial production.
[0028] Other aspects will be apparent upon reading and understanding the drawings and detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings are used to provide further understanding of the technical solution of this article and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the technical solution of this article and do not constitute a limitation on the technical solution of this article.
[0030] Figure 1 The SEM images of the active metal hydroxide (a) and the active metal ternary precursor material (bc) prepared in Example 4 of the present invention; Figure 2 The SEM images of the active metal ternary precursor materials prepared in Comparative Example 1 (a), Comparative Example 2 (b) and Comparative Example 3 (c) of the present invention and the SEM image of the particle cross-section of the active metal ternary precursor material prepared in Comparative Example 4 (d); Figure 3 The SEM images of the active metal ternary single crystal positive electrode materials prepared in Example 4 (a), Comparative Example 1 (b) and Comparative Example 2 (c) of the present invention; Figure 4 It is the XRD diagram of the active metal ternary precursor material prepared in Example 4 and Comparative Examples 1-4 of the present invention. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present disclosure and should not be regarded as specific limitations of the present invention.
[0032] It should be noted that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturers are not specified, are all conventional products that can be purchased commercially.
[0033] The present invention provides a ternary precursor material, which comprises a substrate and a coating layer on the surface of the substrate, wherein the substrate is an active metal hydroxide, and the coating layer is an active metal oxalate; the active metal comprises nickel, cobalt, manganese and N; and the N is selected from one or more doping elements of magnesium, copper, aluminum, titanium, tantalum or niobium.
[0034] In some embodiments, the ternary precursor material satisfies one or more of the following characteristics 1 to 2: Feature 1: The median particle size of the ternary precursor material particles is 5 μm to 7 μm; Feature 2: The carbon content of the ternary precursor material particles is 0.2%~0.5% The carbon content of the ternary precursor material particles can indirectly reflect the oxalate content on the surface of the active metal hydroxide. The more active metal oxalate coating there is, the higher the carbon content of the precursor particles. Furthermore, the more pores the ternary precursor material produces during the subsequent sintering process, and the better the dispersion of the obtained single crystal positive electrode material particles.
[0035] The present invention provides a method for preparing a ternary precursor material, and the preparation method comprises the following steps: S1, first dissolving nickel salt, cobalt salt, manganese salt and N salt in water to obtain a metal salt solution, then adding the metal salt solution, complexing agent and precipitant into a reactor with pure water as the base liquid to carry out a coprecipitation reaction to obtain an active metal hydroxide; S2. Add the oxalic acid solution into the dispersion of the active metal hydroxide, stir and react, and obtain a ternary precursor material.
[0036] The present invention slowly adds oxalic acid solution to the dispersion of active metal hydroxide, and the protons provided by oxalic acid in the solution can react with the hydroxide on the surface of the active metal hydroxide to dissolve some metal ions, and at the same time, the oxalate ions react with these metal ions to obtain active metal oxalate precipitates, which are in-situ deposited and coated on the surface of the active metal hydroxide. The reaction formula is as follows:
[0037] Among them, a+b+c+d=1,0 <a<1,0<b<1,0<c<1,0<d<0.1。
[0038] Specifically, the present invention will explain each of the above steps one by one.
[0039] S1. Add the prepared active metal salt solution, complexing agent and precipitant solution into a reactor with pure water as the base liquid through a metering pump, control the reaction temperature, reaction time, stirring rate and pH value of the reaction liquid, and carry out a coprecipitation reaction. The obtained product is then filtered, washed and dried to obtain an active metal hydroxide.
[0040] In some embodiments, the sum of the molar concentrations of nickel ions, cobalt ions, manganese ions and N ions in the metal salt solution is 1.5~2.5 mol / L, for example, it can be 1.5 mol / L, 2.0 mol / L or 2.5 mol / L, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0041] In some embodiments, in the metal salt solution, based on the total molar number of metal salts being 100 mol, the molar ratio of the nickel salt, the cobalt salt, the manganese salt and the N salt is (35-90):(6-35):(3-35):(1-5), for example, it can be 35:35:28:2, 40:20:35:5 or 90:6:3:1, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0042] In some embodiments, the complexing agent is aqueous ammonia with a molar concentration of 4 to 6 mol / L, for example, 4 mol / L, 5 mol / L or 6 mol / L; the precipitating agent is sodium hydroxide solution or potassium hydroxide solution with a molar concentration of 9 to 11 mol / L, for example, 9 mol / L, 10 mol / L or 11 mol / L, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0043] In some embodiments, the pH value of the coprecipitation reaction is 9-12, for example, 9, 10, 11 or 12, the reaction temperature is 40-70°C, for example, 40°C, 50°C, 60°C or 70°C, the reaction time is 48-72h, for example, 48h, 60h or 72h, and the reaction stirring rate is 300-600r / min, for example, 300r / min, 400r / min, 500r / min or 600r / min, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0044] S2. Slowly add the oxalic acid solution into the dispersion of the active metal hydroxide through a peristaltic pump, and stir the mixture to react at room temperature to obtain an active metal ternary precursor material.
[0045] In some embodiments, the mass concentration of the oxalic acid solution is 100~500g / L, for example, it can be 100g / L, 300g / L or 500g / L, and the mass of oxalic acid in the oxalic acid solution is 10%~80% of the mass of the active metal hydroxide, for example, it can be 10%, 20%, 30%, 50% or 80%, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0046] In some embodiments, the stirring reaction time is 4 to 8 hours, for example, 4 hours, 5 hours, 6 hours, 7 hours or 8 hours, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0047] The amount of oxalic acid used in the present invention will affect the tap density of the precursor. If the amount of oxalic acid used is too much, the amount of oxalate coating on the surface of the active metal ternary precursor is relatively large, and the carbon content of the precursor particles is also higher, which will reduce the tap density of the precursor and thereby reduce the compaction density of the single crystal positive electrode material. If the amount of oxalic acid used is too little, the amount of oxalate coating on the surface of the active metal ternary precursor is relatively small, and the pores generated in the subsequent mixed sintering process with the lithium source are relatively small, and the dispersion of the single crystal positive electrode material is poor.
[0048] The invention provides a ternary positive electrode material. The ternary positive electrode material is prepared by mixing a ternary precursor material with a lithium source and sintering in two stages in an oxygen atmosphere in a muffle furnace.
[0049] In some embodiments, the ratio of the total molar number of the active metal elements to the molar number of the lithium element is 1:(1~1.05), for example, it can be 1:1, 1:1.02, 1:1.03, 1:1.04 or 1:1.05, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0050] In some embodiments, the heating rate of the first sintering stage is 3-5°C / min, for example, 3°C / min, 4°C / min or 5°C / min, the sintering temperature is 650°C-750°C, for example, 650°C, 700°C or 750°C, and the holding time is 3-5h, for example, 3h, 4h or 5h, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0051] In some embodiments, the heating rate of the second sintering is 7-9°C / min, for example, 7°C / min, 8°C / min or 9°C / min, the sintering temperature is 900°C-1000°C, for example, 900°C, 950°C or 1000°C, and the holding time is 9-11h, for example, 9h, 10h or 11h, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0052] The present invention adopts a two-stage sintering process in the process of preparing active metal ternary positive electrode materials: a low-temperature pre-sintering and a high-temperature sintering. The low-temperature pre-sintering temperature is about ~700°C, the pre-sintering heating rate is slow, and the insulation time is short. The low-temperature pre-sintering helps to strengthen the bonding force between the grains while retaining the appropriate pore size and gap; after a certain period of low-temperature pre-sintering, the temperature is directly increased for the second stage of high-temperature sintering. The temperature is generally about ~950°C, the heating rate is fast, and the insulation time is long. The high-temperature sintering further improves the crystallinity and density of the material, and the defects and impurities are repaired and removed, thereby obtaining high-quality single crystal positive electrode materials. The temperature of the two-stage sintering will affect the grain size. If the sintering temperature is too low, the grain size is small; if the sintering temperature is too high, the grain size is too large.
[0053] Example 1 This embodiment provides a method for preparing a ternary precursor material and a positive electrode material, the method comprising the following steps: S1. Nickel sulfate, cobalt sulfate, manganese sulfate and copper sulfate are dissolved in pure water in a molar ratio of Ni, Co, Mn and Cu of 90:6:3:1 to obtain a mixed metal salt solution with a total molar concentration of metal ions of 2 mol / L, and a 10 mol / L sodium hydroxide solution and a 5 mol / L ammonia solution are prepared; then the mixed metal salt solution, the sodium hydroxide solution and the ammonia solution are simultaneously introduced into a stirred reactor with pure water as the base liquid through a metering pump at a flow rate of 5 L / h, a flow rate of 1 L / h and a flow rate of 1 L / h, the reaction temperature is controlled to be 65°C, the reaction time is 60h, the stirring rate is 500r / min and the pH value of the reaction solution is 11.0, a coprecipitation reaction is carried out, and after the reaction is completed, the product is filtered and collected, and the active metal hydroxide is obtained after washing and drying.
[0054] S2, prepare 12L of 500g / L oxalic acid solution, take 20kg of active metal hydroxide and disperse it in pure water, add the oxalic acid solution to the reactor at a rate of 5L / h through a peristaltic pump, maintain the stirring rate at 400r / min, stir and react at room temperature for 8h, then centrifuge, wash, dry, sieve and demagnetize the product to obtain the active metal ternary precursor material. (The mass of oxalic acid is 30% of the mass of active metal hydroxide) S3. The active metal ternary precursor material and lithium hydroxide are mixed evenly at a ratio of 1:1.03 between the total molar number of active metal elements and the molar number of lithium elements, and then two-stage sintering is performed in a muffle furnace under an oxygen atmosphere. The heating rate of the first stage sintering is 4°C / min, the sintering temperature is 700°C, and the holding time is 4h; the second stage sintering is directly performed after the first stage sintering is completed. The heating rate of the second stage sintering is 8°C / min, the sintering temperature is 950°C, and the holding time is 10h. After cooling to room temperature, the sintered product is ground and crushed and passed through a 400-mesh sieve to obtain an active metal ternary single crystal positive electrode material.
[0055] Example 2 This embodiment provides a method for preparing a ternary precursor material and a positive electrode material, the method comprising the following steps: S1. Nickel sulfate, cobalt sulfate, manganese sulfate and copper sulfate are dissolved in pure water in a molar ratio of Ni, Co, Mn and Cu of 35:35:28:2 to obtain a mixed metal salt solution with a total molar concentration of metal ions of 1.5 mol / L, and a 9 mol / L sodium hydroxide solution and a 4 mol / L ammonia solution are prepared; then the mixed metal salt solution is introduced into a stirred reactor with pure water as the base liquid at a flow rate of 5 L / h, the sodium hydroxide solution is introduced at a flow rate of 1 L / h, and the ammonia solution is introduced at a flow rate of 1 L / h through a metering pump at the same time, and the reaction temperature is controlled to be 40°C, the reaction time is 48 h, the stirring rate is 300 r / min and the pH value of the reaction solution is 9.0, and a coprecipitation reaction is carried out. After the reaction is completed, the product is filtered and collected, and the active metal hydroxide is obtained after washing and drying.
[0056] S2, prepare 33.4L of 300g / L oxalic acid solution, take 20kg of active metal hydroxide and disperse it in pure water, add the oxalic acid solution to the reactor at a rate of 5L / h through a peristaltic pump, maintain the stirring rate at 400r / min, stir and react at room temperature for 6h, then centrifuge, wash, dry, sieve and demagnetize the product to obtain the active metal ternary precursor material. (The mass of oxalic acid is 50% of the mass of active metal hydroxide) S3. The active metal ternary precursor material and lithium hydroxide are mixed evenly in a ratio of 1:1 between the total molar number of active metal elements and the molar number of lithium elements, and then two-stage sintering is performed in a muffle furnace under an oxygen atmosphere. The heating rate of the first stage sintering is 3°C / min, the sintering temperature is 650°C, and the holding time is 3h; the second stage sintering is directly performed after the first stage sintering is completed. The heating rate of the second stage sintering is 7°C / min, the sintering temperature is 900°C, and the holding time is 9h. After cooling to room temperature, the sintered product is ground and crushed and passed through a 400-mesh sieve to obtain an active metal ternary single crystal positive electrode material.
[0057] Example 3 This embodiment provides a method for preparing a ternary precursor material and a positive electrode material, the method comprising the following steps: S1. Nickel sulfate, cobalt sulfate, manganese sulfate and copper sulfate are dissolved in pure water in a molar ratio of Ni, Co, Mn and Cu of 40:20:35:5 to obtain a mixed metal salt solution with a total molar concentration of metal ions of 2.5 mol / L, and 11 mol / L sodium hydroxide solution and 6 mol / L ammonia water are prepared; then the mixed metal salt solution is introduced into a stirred reactor with pure water as the base liquid at a flow rate of 5 L / h, the sodium hydroxide solution is introduced at a flow rate of 1 L / h, and the ammonia water is introduced at a flow rate of 1 L / h through a metering pump at the same time, and the reaction temperature is controlled to be 70°C, the reaction time is 72 h, the stirring rate is 600 r / min and the pH value of the reaction solution is 12.0 to carry out a coprecipitation reaction. After the reaction is completed, the product is filtered and collected, and the active metal hydroxide is obtained after washing and drying.
[0058] S2, prepare 20L of 100g / L oxalic acid solution, take 20kg of active metal hydroxide precursor and disperse it in pure water, add the oxalic acid solution to the reactor at a rate of 5L / h through a peristaltic pump, maintain the stirring rate at 400r / min, stir and react at room temperature for 4h, then centrifuge, wash, dry, sieve and demagnetize the product to obtain the active metal ternary precursor material. (The mass of oxalic acid is 10% of the mass of active metal hydroxide) S3. The active metal ternary precursor material and lithium hydroxide are mixed evenly at a ratio of 1:1.05 between the total molar number of active metal elements and the molar number of lithium elements, and then two-stage sintering is performed in a muffle furnace under an oxygen atmosphere. The heating rate of the first stage sintering is 5°C / min, the sintering temperature is 750°C, and the holding time is 5h; the second stage sintering is directly performed after the first stage sintering is completed. The heating rate of the second stage sintering is 9°C / min, the sintering temperature is 1000°C, and the holding time is 11h. After cooling to room temperature, the sintered product is ground and crushed and passed through a 400-mesh sieve to obtain an active metal ternary single crystal positive electrode material.
[0059] Example 4 Compared with Example 1, the amount of oxalic acid solution in step S2 is changed to 20 L, the mass of oxalic acid is 50% of the mass of active metal hydroxide, and the other steps remain unchanged.
[0060] Example 5 Compared with Example 1, the amount of oxalic acid solution in step S2 is changed to 32 L, the mass of oxalic acid is 80% of the mass of active metal hydroxide, and the other steps remain unchanged.
[0061] Example 6 Compared with Example 1, the amount of oxalic acid solution in step S2 is changed to 4 L, the mass of oxalic acid is 10% of the mass of active metal hydroxide, and the other steps remain unchanged.
[0062] Example 7 Compared with Example 2, the mass concentration of the oxalic acid solution in step S2 is changed to 200 g / L, the amount is changed to 50 L, and the other steps remain unchanged.
[0063] Example 8 Compared with Example 2, the mass concentration of the oxalic acid solution in step S2 is changed to 400 g / L, the dosage is changed to 25 L, and the other steps remain unchanged.
[0064] Example 9 Compared with Example 1, the first-stage sintering temperature in step S3 is changed to 650° C., the second-stage sintering temperature is changed to 900° C., and the other steps remain unchanged.
[0065] Example 10 Compared with Example 1, the first-stage sintering temperature in step S3 is changed to 750° C., the second-stage sintering temperature is changed to 1000° C., and the other steps remain unchanged.
[0066] Comparative Example 1 In this comparative example, a ternary precursor material and a ternary positive electrode material in which the surface of an active metal hydroxide is not coated with an active metal oxalate are prepared. The preparation method comprises the following steps: Compared with Example 4, step S2 is not performed and the remaining steps remain unchanged.
[0067] Comparative Example 2 The ternary precursor material prepared in this comparative example adopts a non-in-situ coating method, wherein an active metal hydroxide is mixed as a seed with a mixed liquid of a metal liquid containing an active metal and oxalic acid. The preparation method comprises the following steps: S1. Same as step S1 of embodiment 4.
[0068] S2, prepare 20L of 500g / L oxalic acid solution, take 20kg of active metal hydroxide and disperse it in pure water, add the metal liquid containing active metal and oxalic acid solution at 5L / h to the reactor slowly through a peristaltic pump at the same time, maintain the stirring rate at 400r / min, stir and react at room temperature for 8h, then centrifuge, wash, dry, sieve and demagnetize the product to obtain the active metal ternary precursor material. (The mass of oxalic acid is 50% of the mass of active metal hydroxide) S3. The same as step S3 of embodiment 4.
[0069] Comparative Example 3 In this comparative example, oxalic acid and sodium hydroxide are used as coprecipitants to prepare an active metal oxalate / active metal hydroxide composite precursor material and a positive electrode material thereof. The preparation method comprises the following steps: S1. Nickel sulfate, cobalt sulfate, manganese sulfate and copper sulfate are dissolved in pure water at a molar ratio of Ni, Co, Mn and Cu of 90:6:3:1 to obtain a mixed metal salt solution with a total molar concentration of metal ions of 2 mol / L, and 10 mol / L sodium hydroxide solution, 5 mol / L oxalic acid solution and 5 mol / L ammonia water are prepared; then the mixed metal salt solution is introduced into a stirred reactor with pure water as the base liquid at a flow rate of 5 L / h, the sodium hydroxide solution is introduced at a flow rate of 1 L / h, and the ammonia water is introduced at a flow rate of 1 L / h through a metering pump at the same time, and the reaction temperature is controlled to be 65°C, the reaction time is 60h, the stirring rate is 500r / min and the pH value of the reaction solution is 11.0 to carry out a coprecipitation reaction. After the reaction is completed, the product is filtered and collected, and an active metal oxalate / active metal hydroxide composite precursor material is obtained after washing and drying.
[0070] S2. Evenly mix the active metal oxalate / active metal hydroxide composite precursor material and lithium hydroxide in a ratio of 1:1.05 between the total molar number of active metal elements and the molar number of lithium elements. The remaining steps are the same as step S3 of Example 4.
[0071] Comparative Example 4 In this comparative example, a ternary precursor material and a ternary positive electrode material with an active metal oxalate / active metal hydroxide complex as a matrix and an active metal hydroxide as a coating layer are prepared. The preparation method includes the following steps: S1. According to the molar ratio of Ni, Co, Mn and Cu elements of 90:6:3:1, nickel sulfate, cobalt sulfate, manganese sulfate and copper sulfate are dissolved in pure water to obtain a mixed metal salt solution with a total molar concentration of metal ions of 2 mol / L, and 10 mol / L sodium hydroxide solution, 5 mol / L oxalic acid solution and 5 mol / L ammonia water are prepared; then the mixed metal salt solution is fed into the mixing tank at a flow rate of 5 L / h, the sodium hydroxide solution is fed at a flow rate of 1 L / h, and the ammonia water is fed into the mixing tank at a flow rate of 1 L / h through a metering pump. In a stirred reactor with pure water as the base liquid, the reaction temperature is controlled to be 65°C, the reaction time is 60h, the stirring rate is 500r / min and the pH value of the reaction liquid is 11.0, and a coprecipitation reaction is carried out. When the particle size reaches 2.0um, the addition of oxalic acid solution is stopped, and the reaction is continued with sodium hydroxide as the only precipitant. The obtained product is filtered, washed, and dried to obtain an active metal ternary precursor material with an active metal oxalate / active metal hydroxide complex as a matrix and an active metal hydroxide as a coating layer.
[0072] S2. The same as step S3 of Example 4.
[0073] The active metal ternary positive electrode materials prepared in Examples 1 to 10 and Comparative Examples 1 to 4 were assembled into button cells and their electrochemical performance was evaluated, specifically comprising the following steps: (1) Preparation of button cells The active metal ternary single crystal positive electrode material was homogenized in a mass ratio of positive electrode: conductive agent: binder = 80:10:10, and the slurry was evenly coated on the grade sheet with a coating surface density of 20 mg / cm 2 , place the electrode in an oven and dry it at 80°C for 8 hours; then roll and take out the electrode, assemble the electrode, diaphragm and negative electrode in a glove box, inject electrolyte and assemble into a button battery.
[0074] (2) Particle size test The particle size of the active metal ternary precursor material was tested using a GSL-101BI laser particle size analyzer.
[0075] (3) Carbon content test The active metal ternary precursor powder is placed in a sulfur-carbon tester to test its carbon content.
[0076] (4) Compaction density test The active metal single crystal ternary cathode material powder was placed in a FTYS-50KN compaction density tester and its compaction density was tested at 200 MPa.
[0077] (5) Electrochemical performance test At 25°C, the charge and discharge cycle characteristics of the button cell were tested using a blue power test cabinet. The charge and discharge test was performed at a charge and discharge rate of 0.1C in the voltage range of 2.8V-4.3V. The results are shown in Table 1.
[0078] Table 1
[0079] From the attached figure, it can be concluded that: Figure 1 a. Figure 2 a is the SEM image of active metal hydroxide before coating. Figure 1 b is the SEM image of the active metal ternary cathode precursor obtained after coating with active metal oxalate. Figure 1 b It can be seen that the morphology of the active metal hydroxide changes significantly after being coated with the active metal oxalate, and the active metal oxalate is distributed on the surface of the active metal hydroxide in a granular form.
[0080] From Comparative Example 2 ( Figure 2 b) and Example 4 ( Figure 1bc) SEM images show that more small particles appear around the active metal ternary precursor prepared by non-in-situ coating in Comparative Example 2, because the precipitated active metal oxalate nucleates alone and is not coated on the surface of the active metal hydroxide; there are no obvious small particles around the active metal ternary precursor prepared by in-situ coating in Example 4, and the active metal oxalate is uniformly coated on the surface of the active metal hydroxide, avoiding the nucleation of oxalate alone. Figure 2 c) and Example 4 ( Figure 1 c) shows that the surface of the active metal oxalate / active metal hydroxide composite precursor prepared in Comparative Example 3 is fuzzy and the primary particles are unclear. This is because the generated active metal oxalate is easily dissolved again in an alkaline environment. Figure 2 d) The particle cross-section SEM image shows that the core-shell structure of the active metal ternary precursor is hollow inside. The reason is that when the active metal oxalate / active metal hydroxide crystal core is in an alkaline environment, the oxalate will dissolve, resulting in a hollow inside.
[0081] According to Comparative Example 1 ( Figure 3 b), Comparative Example 2 ( Figure 3 c) and Example 4 ( Figure 3 a) From the SEM image of the prepared active metal single crystal ternary positive electrode material, it can be seen that the single crystal ternary positive electrode particles prepared by sintering and crushing the active metal ternary precursor of Example 4 have basically no agglomeration phenomenon, and therefore have better dispersibility.
[0082] according to Figure 4 From the XRD diagram of the active metal ternary precursor material, it can be obtained that compared with the XRD curve of Comparative Example 1, the active metal hydroxide prepared in Example 4 has an obvious nickel oxalate phase after oxalate coating. The XRD curves of Comparative Example 2 and Example 4 show that nickel oxalate phases exist in both active metal ternary precursors. Compared with the XRD curve of Example 4, the proportion of oxalate phase in the active metal oxalate / active metal hydroxide composite precursor prepared in Comparative Example 3 is significantly lower, because the generated oxalate is easily dissolved again in an alkaline environment; the oxalate phase is almost invisible in the core-shell structure active metal ternary precursor prepared in Comparative Example 4, because the oxalate in the active metal oxalate / active metal hydroxide crystal nucleus is easily dissolved in an alkaline environment.
[0083] From Table 1 we can see that: It can be seen from Examples 1-10 that for the lithium-ion button battery composed of the active metal ternary positive electrode material prepared by the method of the present invention, when the oxalic acid coating amount is 10-50%, the compaction density of the single crystal positive electrode material is high, and the discharge capacity and cycle performance are significantly improved compared with the uncoated sample, but when the coating amount is too high (for example, 80%), the compaction density of the single crystal positive electrode material is significantly reduced.
[0084] By comparing Example 1 with Examples 4-6, it can be seen that in the preparation process of the active metal ternary precursor and the positive electrode material of the present invention, the coating amount of the active metal oxalate on the surface of the active metal hydroxide will affect its performance. If the coating amount is too low (for example, a 10% coating amount), the discharge capacity is low and the cycle performance is poor; if the coating amount is too high (for example, an 80% coating amount), the compaction density decreases significantly, the discharge capacity is low, and the cycle performance is poor.
[0085] By comparing Example 2 with Examples 7-8, it can be seen that in the preparation process of the active metal ternary precursor and the positive electrode material of the present invention, the mass concentration of the oxalic acid solution will not affect its compaction density, discharge capacity and cycle performance.
[0086] By comparing Example 1 with Examples 9-10, it can be seen that in the preparation process of the active metal ternary precursor and the positive electrode material of the present invention, the temperature of the two-stage sintering will affect its performance. If the sintering temperature is too high, the grain size is larger, the compaction density increases, but the discharge capacity is low, and the cycle performance increases; if the sintering temperature is too low, the grain size is smaller, the compaction density decreases, the discharge capacity is high, but the cycle performance is poor.
[0087] It can be concluded from Examples 1, 4, 6 and Comparative Example 1 that after the active metal hydroxide is in-situ coated with the active metal oxalate, an active metal ternary precursor material and its positive electrode material are obtained, and the discharge capacity and cycle performance of the lithium ion battery prepared therefrom are significantly improved, and with the increase of the active metal oxalate coating amount, the higher the discharge capacity, the better the cycle performance, because the coated active metal oxalate decomposes and produces gas to form a pore structure during the sintering process, which will significantly improve the dispersibility of the ternary single crystal positive electrode material particles and make the particle size distribution of the single crystal particles more uniform.
[0088] It can be concluded from Example 4 and Comparative Example 2 that, under the same active metal oxalate coating amount, the discharge capacity and cycle performance of the lithium-ion battery can be significantly improved by coating oxalate on the surface of the active metal hydroxide in situ. The reason is that the active metal oxalate obtained by the in-situ coating has better uniformity, while the non-in-situ coating method is prone to the phenomenon of oxalate nucleation alone. During the sintering process, the active metal oxalate nucleated alone will decompose rapidly to form micropowder, resulting in large differences in the particle size of the ternary single crystal positive electrode material particles, which is not conducive to the capacity and deteriorates the cycle.
[0089] It can be concluded from Example 4 and Comparative Example 3 that due to the low oxalate content in the active metal oxalate / active metal hydroxide composite precursor, the discharge capacity and cycle performance of the lithium ion battery of Comparative Example 3 are lower than those of Example 4. The reason is that oxalate is unstable in an alkaline environment and easily decomposes, resulting in a low oxalate phase in the active metal oxalate / active metal hydroxide composite precursor, less gas production during sintering, and thus fewer pore structures, which is not conducive to the dispersion of the ternary single crystal positive electrode material particles, and the particle size distribution of the single crystal particles is widened, which is not conducive to improving the discharge capacity and cycle performance of the lithium ion battery.
[0090] It can be concluded from Example 4 and Comparative Example 4 that since Comparative Example 4 is a core-shell structured active metal ternary precursor material with an active metal oxalate / active metal hydroxide composite precursor as the core and an active metal hydroxide as the shell, the oxalate content in the core layer active metal oxalate / active metal hydroxide is extremely low, and its lithium ion battery discharge capacity and cycle performance are lower than those of Example 4. The reason is that the oxalate in the active metal oxalate / active metal hydroxide crystal core is unstable in an alkaline environment and is easily dissolved, resulting in hollow particles. During the sintering process, due to the extremely low oxalate content, fewer pore structures are generated. In addition, hollow structures appear inside some particles, which deteriorates the discharge capacity and cycle performance of the ternary single crystal positive electrode material.
[0091] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A ternary precursor material, characterized in that: The ternary precursor material includes a substrate and a coating layer on the surface of the substrate, the substrate is an active metal hydroxide, and the coating layer is an active metal oxalate; the active metal includes nickel, cobalt, manganese and N; the N is selected from one or more doping elements of magnesium, copper, aluminum, titanium, tantalum or niobium.
2. The ternary precursor material according to claim 1, characterized in that: The ternary precursor material satisfies one or more of the following characteristics 1 to 2: Feature 1: The median particle size of the ternary precursor material particles is 5 μm to 7 μm; Feature 2: The carbon content of the ternary precursor material particles is 0.2%~0.5%.
3. A method for preparing a ternary precursor material according to any one of claims 1 to 2, characterized in that: The following steps are involved: The oxalic acid solution is added into the dispersion of the active metal hydroxide, and the mixture is stirred for reaction to obtain a ternary precursor material.
4. The method for preparing the ternary precursor material according to claim 3, characterized in that: The preparation method of the active metal hydroxide comprises: dissolving nickel salt, cobalt salt, manganese salt and N salt in water to obtain a metal salt solution, and then adding the metal salt solution, a complexing agent and a precipitant into a reaction kettle with pure water as a base liquid to perform a coprecipitation reaction.
5. The method for preparing the ternary precursor material according to claim 4, characterized in that: The nickel salt, the cobalt salt, and the manganese salt include at least one of sulfate, chloride, and nitrate; or / and, the N salt comprises at least one of soluble salts of magnesium, copper, aluminum, titanium, tantalum and niobium; Or / and, the sum of the molar concentrations of nickel ions, cobalt ions, manganese ions and nitrogen ions in the metal salt solution is 1.5-2.5 mol / L; Or / and, in the metal salt solution, based on the total molar number of metal salts being 100 mol, the molar ratio of the nickel salt, the cobalt salt, the manganese salt and the N salt is (35-90): (6-35): (3-35): (1-5); Or / and, the complexing agent is ammonia water with a molar concentration of 4-6 mol / L; Or / and, the precipitant is a sodium hydroxide solution or a potassium hydroxide solution with a molar concentration of 9 to 11 mol / L; Or / and, the pH value of the coprecipitation reaction is 9-12, the reaction temperature is 40-70° C., the reaction time is 48-72 h, and the reaction stirring rate is 300-600 r / min.
6. The method for preparing the ternary precursor material according to claim 3, characterized in that: The mass concentration of the oxalic acid solution is 100-500 g / L; Or / and, the mass of oxalic acid in the oxalic acid solution is 10% to 80% of the mass of the active metal hydroxide; Or / and, the stirring reaction temperature is room temperature, and the reaction time is 4 to 8 hours.
7. A ternary positive electrode material, characterized in that: The ternary positive electrode material is prepared by mixing the ternary precursor material according to claim 1 or 2 with a lithium source and sintering the mixture.
8. The ternary cathode material according to claim 7, characterized in that: The lithium source includes at least one of lithium hydroxide, lithium acetate and lithium oxalate; Or / and, the ratio of the total molar number of the active metal elements to the molar number of the lithium element is 1:(1-1.05).
9. The ternary cathode material according to claim 7, characterized in that: The sintering includes two stages of sintering. The first stage of sintering is to heat up to 650°C~750°C at a heating rate of 3~5°C / min and keep warm in an oxygen atmosphere for 3~5 hours. The second stage of sintering is to heat up to 900°C~1000°C at a heating rate of 7~9°C / min and keep warm in an oxygen atmosphere for 9~11 hours.
10. Use of the ternary cathode material according to any one of claims 7 to 9 in the preparation of lithium-ion batteries.
Citation Information
Patent Citations
Surface in-situ coated lithium-enriched material and preparation method thereof
CN106486657A
Preparation method and application of no-clean high-nickel single-crystal lithium nickel cobalt manganate positive electrode material
CN111916724A
Preparation method of ternary precursor modified through coating with multivalent metal phosphide
CN113307314A
Ultrahigh nickel single crystal ternary positive electrode material with cobalt-doped surface, preparation method thereof and lithium ion battery
CN116947122A
Cited By
Nanometer flaky ternary precursor as well as preparation method and application thereof
CN120440983A
Monocrystal ternary positive electrode material, preparation method thereof and lithium ion battery
CN121110154A